Temporal trends of food insecurity in Chad, 2016–2021 - Kang, Yunhee; Wabyona, Edgar; Etienne, Kississou; Allarabaye, Madjioudal; Bakoi, Abel; Doocy, Shannon (Frontiers in Sustainable Food Systems, 2023)
Considering persistently high levels of poverty and food insecurity in Chad, this study examines food insecurity trends from 2016 to 2021 and identifies risk factors for food insecurity in 2020 and 2021. Data from six cross-sectional Enquête Nationale sur la Security Alimentaire (ENSA) surveys from 2016 to 2021 collected in rural areas were used. The linear regressions for food consumption score (FCS), reduced coping strategy index (rCSI), and livelihood coping strategy index (LCSI) and logistic regressions for "poor food consumption" was used to estimate the annual rate of change. Risk factor analysis was conducted with demographic, socio-economic, and pandemicrelated economic indicators in univariate models, and subsequent multivariate models were used to produce adjusted odds ratios. At a national level, there was a gradual decrease in FCS (1.16 points per year) and an increase in LCSI (0.11 points) and an increase in the proportion of households with poor food consumption from 18.5% to 25.3% (1.55 percentage point) during 2016-2021; a similar trend for FCS and LCSI for worsened food insecurity was observed in the Sudanian zone. There was no significant change in rCSI during that time at the national level but there was a reduction in the Saharan zone and an increasing trend in Sahélian zone. Risk factors for poor food consumption in 2020-2021 included lower wealth status, a single income source, an illiterate household head, and Sahelian zone residence. The only characteristic significantly associated with increased coping mechanism use in both years was having a disabled household head. The results provide evidence of worsening food security in Chad in the past six years, both nationally and including the agricultural Sudanian zone. Food insecurity was consistently the highest in the Sahelian zone. While some risk factors for poor food consumption and diet-related coping mechanism use were consistent between 2020 and 2021, there were differences among other risk factors, likely a reflection of impacts of the COVID-19 pandemic. A strategic shift in humanitarian and development programming is required to mitigate the rise in food insecurity at the national and regional levels, with a particular emphasis on the Sahelian zone.